Measuring user satisfaction: A service quality analysis of the Bengkulu Province library and archives - Valentino, Rahmat Alifin; Nurdiansyah, Aulia (Jurnal Informatio, 2025)
Background: The Bengkulu Province Library and Archives, as a public library, needs to continuously evaluate its services to ensure quality and enhance user satisfaction.Purpose: This study aims to assess the quality of services at the Bengkulu Province Library and Archives using the LibQual framework.Methods: A quantitative approach was employed with 91 respondents selected through purposive sampling. Data were collected using structured questionnaires and analyzed based on the three LibQual dimensions: Affect of Service, Information Control, and Library as Place.Results: The findings show that users are generally satisfied with the Affect of Service and Library as Place dimensions, as indicated by positive adequacy gaps. However, reliability in service delivery remains a critical weakness that may reduce user trust and loyalty. Furthermore, the Information Control dimension received lower ratings, particularly regarding equipment in the library, timeliness in locating required collections, and the limited availability of relevant materials. Inadequate information content coverage and limited technological facilities highlight the urgency of expanding digital collections and upgrading equipment to better align with user expectations.Conclusions: Overall, users perceive the library’s services as fairly satisfactory, but improvements are needed in strengthening information control, especially in enhancing staff efficiency and ensuring the availability of relevant resources. These findings highlight the importance of improving services, information access, and technological facilities to strengthen user satisfaction and loyalty.